Development of 2D Animation Video Learning Media Mukashibanashi: Saru Kani Gassen at SMA Negeri 12 Bekasi - Erlina Yuliana; Hamidillah Ajieb; Murien Nugrahenic (Universitas Pendidikan Indonesia, 2024)
According to a poll done in 2021 by The Japan Foundation, Indonesia has the second-highest population of Japanese language learners worldwide. Japanese is now available for study in schools as one of the specialized courses, according to the government. Using learning material is one way to try and maximize the learning process. Learning materials for Mukashibanashi material: Saru Kani Gassen at SMA Negeri 12 Bekasi City are still ineffective, according to the interview's findings. Based on this, Mukashibanashi: Saru Kani Gassen, a 2D animated film, was created as educational material to assist third-grade high school students at SMA Negeri 12 Bekasi City in their studying. The Multimedia Development Life Cycle (MDLC) approach is used in this learning media development to create a 2D animation video that lasts 6 minutes and 40 seconds in mp4 format. Two testing phases, known as alpha and beta testing, are used to conduct feasibility testing on 2D animation video learning media products. A percentage of 89% was obtained from the feasibility test results, placing the responders in the